Antimicrobial activity of CT-K3K7, a modified peptide by lysine substitutions from ctry2459 - A Chaerilus tryznai scorpion venom peptide. (30th October 2022) - Li, Shasha; Shui, Yingbin; Ma, Jiayue; Yuan, Yaping; Jiang, Wenxing; Xu, Chenxi; Wang, Lejing; Ren, Yongjing; Deng, Bo; Zhang, Wenlu; Li, Zhongjie
Abstract: Antimicrobial peptides (AMPs) have started to garner more interest as novel antimicrobial agents. The scorpion venom peptide ctry2459 was modified to CT-K3K7 by lysine substitutions at the 3rd and 7th positions to increase the cationic properties. We discovered that the modified peptides CT-K3K7 had improved antibacterial activity, higher thermal stability, as well as lower hemolytic activity. It can kill S. aureus and P. aeruginosa rapidly, and reduce the production of biofilm and live bacterial residues in biofilm in vitro. CT-K3K7 has also been demonstrated to decrease bacterial counts, abscess area, and inflammatory cell infiltration in the mouse subcutaneous abscess models that were duplicated by S. aureus and P. aeruginosa . CT-K3K7 has difficulty in inducing S. aureus and P. aeruginosa to develop drug resistance, which may be related to the bactericidal properties. CT-K3K7 increases cationic properties by lysine substitutions can increase the electrostatic force between the peptides and the bacterial surface, which can lead to an increase in bacterial membrane permeability and DNA binding. In conclusion, the modified peptide CT-K3K7 enhances the antimicrobial activity and can be a novel antimicrobial agent candidate for the treatment of infections by S. aureus and P. aeruginosa . Graphical abstract: Image 1 Highlights: The peptide CT-K3K7, modified by a lysine substitution had a stronger bactericidal effect. CT-K3K7 could eliminate Staphylococcus aureus and Pseudomonas aeruginosa in vitro, and reduce the production of biofilm. CT-K3K7 has been proven to have a bactericidal effect on the subcutaneous abscess model in mice. The bactericidal mechanism of CT-K3K7 can destroy bacterial membranes and bind to the DNA through electrostatic force.